Atypical genital herpes in a child: a case report - Xia QIN; Guiyan DENG; Xiangui CHENG; Lingyan WU (editoiral office of Journal of Diagnosis and Therapy on Dermato-venereology, 2023)
A case of atypical genital herpes in a child is reported. A 2-year-old girl presented with blisters sized from rice to green bean and some erosion on the vulva, bilateral medial femur and perianal area for 3 days. Some blisters appeared umbilicated with thick wall, clear fluid and erosion, but without lymphadenopathy. Herpes simplex virus Ⅱ-DNA and serum HSV-Ⅱ IgM were positive. A diagnosis of genital herpes was made. Lesions were improved after one week of antiviral therapy. No recurrence was observed during 1-year follow-up.